1989
DOI: 10.1002/jcp.1041410311
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of insulin internalization and processing in adipocytes: Effects of insulin concentration

Abstract: We have studied the effect of insulin concentration on the kinetics of insulin internalization and efflux in isolated rat adipocytes. To determine internalization rates adipocytes were incubated with 125I-insulin at 37 degrees C; and at frequent, early time points surface-bound and intracellular insulin were quantitated. Surface-bound and intracellular insulin were discriminated by the sensitivity of the former to rapid dissociation by a pH 3.0 buffer at 4 degrees C. From this data the endocytotic (internaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…Similar to many cell surface receptors, the insulin receptor is internalized into intracellular vesicular compartments following ligand binding and tyrosine kinase activation (3,28,35,37). Recent studies have begun to examine the structural determinants required for insulin receptor endocytosis (2,4,5,7,8,13,24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to many cell surface receptors, the insulin receptor is internalized into intracellular vesicular compartments following ligand binding and tyrosine kinase activation (3,28,35,37). Recent studies have begun to examine the structural determinants required for insulin receptor endocytosis (2,4,5,7,8,13,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…These include down regulation of cell surface receptors, degradation of the receptor and/or ligand, absorption and retention of essential nutrients, transcellular transport of specific ligands, and the activation of intracellular signal transduction cascades (42,49,52). It is well established that the insulin receptor undergoes endocytosis upon insulin stimulation (3,28,35,37); however, the exact physiological significance of insulin receptor internalization is poorly understood. Several studies have demonstrated that following insulin stimulation, the endosome-localized insulin receptor exhibits increased autophosphorylating and exogenous substrate tyrosine kinase activity compared to plasma membrane-associated insulin receptors (3,31,32).…”
mentioning
confidence: 99%
“…Also, it was shown that insulin was absorbed through receptor-mediated endocytosis in cultured HT-29 cells, 31 a cell line derived from human colon carcinoma. Furthermore, insulin was absorbed through fluid-phase endocytosis at high concentrations, [32][33][34] and intracellular trafficking of insulin via the cytosol compartment has been observed. 35,36 Thus, the metabolism of insulin by cytosolic IDE must be considered with regard to insulin absorption.…”
Section: Methodsmentioning
confidence: 97%
“…Firstly, a higher DI may be due to a hyperinsulinemia relative to the the level of S I . However, hyperinsulinemia has been associated with lower insulin clearance in both adipose tissue [33] and muscle [34], due to reduced a nity of insulin receptors at these sites, and is therefore an unlikely explanation for our nding of a higher CLp relative to higher DI. Secondly, a higher DI could be due to a greater S I in relation to the level of AIRg.…”
Section: Associates With Peripheral Insulin Clearancementioning
confidence: 78%
“…In this scenario, a higher CLp may be due to enhanced binding of insulin to insulin receptors in peripheral tissues. Although a positive association has been demonstrated between S I and hepatic insulin clearance [35], no association between insulin internalization, a measure of insulin clearance, and S I was observed in rat adipocytes [33], whereas the association between S I and insulin clearance in muscle is unknown. However, in support of the second scenario, we showed that those with the highest DI and CLp were also more insulin sensitive, but only exhibited a slightly higher AIRg compared to those with lower DI and CLp.…”
Section: Associates With Peripheral Insulin Clearancementioning
confidence: 97%